Factors To Influence Employee Performance In Bank Tabungan Negara Sharia Semarang - Avita Puji Ilahi; Arif Afendi (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
AbstractPurpose - This research aimed to know the analysis of the influence of work experience, education, and work motivation on the employees’ performance of BTN Syariah KCS Semarang..Method - This research used primary data namely questionnaire which used Likert scale as the calculation scale, and also documentation given by the employees’ of BTN Syariah KCS Semarang. The samples of this research were 73 employees’. To analyse the data, the writer used multiple linier regression method and SPSS 16 version.Result - The result of the research showed that work experience had positive and significant effect toward employees’ performance, education had positive and significant effect toward employees’ performance, and work motivation had positive but nit significant effect toward employees’ performance. It showed that work experience, education, and work motivation had positive and significant effect toward employees’ performance.Implication - This study uses the data from only one Islamic bank.Originality - The paper looks into the determinant factors ofemployees’ performance at BTN Syariah Semarang. Previous studies have only focused on employees’ performance in conventional banks. On the other hand, this paper contributes to the empirical literature, giving a clearer picture of the determinants of employees’ performance of Islamic banks.